Cranial osteology of meiglyptini (aves: piciformes: picidae) - Donatelli, Reginaldo José [UNESP] (Hindawi, 2012)
The Meiglyptini comprise eight species grouped into three genera: Meiglyptes and Mulleripicus, with three species each, and Hemicircus, with two species. The aim of the present study was to describe the cranial osteology of six species and three genera of Meiglyptini and to compare them to each other, as well as with other species of woodpeckers and other bird groups. The cranial osteology varied among the investigated species, but the most markedly distinct characteristics were: (1) a frontal overhang is only observed in the middle portion of the frontale of H. concretus; (2) the Proc. zygomaticus and suprameaticus are thick and long in species of the genus Mulleripicus, but short in other species; (3) the Pes pterygoidei is relatively larger in species of the genus Mulleripicus, while it is narrow, thin and relatively smaller in species of the genus Meiglyptes and indistinct in H. concretus; (4) the bony projection of the ectethmoidale is relatively short and thin in species of Mulleripicus and more developed in H. concretus. It appears that the greatest structural complexity of the cranial osteology is associated with the birds' diet, with the frugivorous H. concretus being markedly different from the insectivorous species.